THE ROLE OF SOCIAL MEDIA IN MSME INTERNATIONAL MARKETING PRACTICES (CASE STUDY OF RARAGU CRAFT PASURUAN) - Suratno Suratno; Sudarmiatin Sudarmiatin; Imam Mukhlis (Sean Institute, 2022)
Studies on the use and effectiveness of social media in large companies abound in the literature. However, the use of social media for relationship marketing in small and medium enterprises is still under-researched. This study examines how social media influences SME's international relations with their customers. Technology Affordance theory is used as a theoretical framework. Furthermore, the case study is used as a research design. The research participants were owners/managers of UKM Raragu Craft Pasuruan. Thematic analysis techniques were used to analyze the data. This study identified three social media capabilities in the context of relationship marketing in UKM Raragu Craft Pasuruan: brand visibility, sharing, and relationships. This social media capability results in customer acquisition. The findings and their implications have been discussed in this article..